PENERAPAN MODEL KURIKULUM TERPADU MATA PELAJARAN KKPI KOMPETENSI DASAR MENGOPERASIKAN SOFTWARE PENGOLAH KATA UNTUK MENINGKATKAN KETERAMPILAN MENULIS SURAT LAMARAN PEKERJAAN (Innovative Journal of Curriculum and Educational Technology, 2012)
Surat  lamaran  pekerjaan merupakan  salah  satu  jenis  surat  yang perlu  dikuasai  oleh  siswa  SMK  guna menghadapi  dunia  kerja. Keterampilan membuat  surat  lamaran  pekerjaan,  saat  ini  di  SMK diajarkan pada mata pelajaran KKPI  (Keterampilan Komputer dan Pengelolaan Informasi), Bahasa Indonesia dan Bahasa  Inggris. Dua model  kurikulum  terpadu  yaitu  threaded  dan  connected mendorong  peneliti  untuk mendeskripsikan penerapan serta melihat seberapa peningkatan keterampilan siswa dalam menulis surat lamaran pekerjaan  setelah penerapan model. Teknik pengumpulan  data menggunakan  teknik  tes  unjuk kerja, observasi dan wawancara. Pengolahan data dimulai dengan pengambilan data, reduksi data, paparan data,  analisis  data dan  simpulan. Penerapan kurikulum  terpadu baik  threaded maupun  connected dalam penerapannya  mempunyai  kesamaan  dalam  hal  materi  yang diajarkan,  yaitu  pengoperasian  aplikasi pengolah  kata dan  surat lamaran pekerjaan berbahasa  Indonesia dan  berbahasa  Inggris. Perbedaannya, kelas  threaded  diajarkan  dengan  team  teaching oleh  guru  KKPI,  Bahasa  Indonesia  dan  bahasa  Inggris sedangkan connected diajarkan oleh guru tunggal yaitu guru KKPI. Model kurikulum  terpadu Threaded maupun Connected sama-sama menunjukkan peningkatan keterampilan menulis surat lamaran pekerjaan, meski  demikian  tidak  terdapat  perbedaan  peningkatan yang  signifikan  antara  keduanya.  Threaded mempunyai kelebihan yaitu dengan team teaching yang terdiri atas beberapa guru menjadikan pengalaman dan  pemahaman  peserta  didik  lebih  kaya. Kelebihan  dalam  pelaksanaan  connected  adalah  guru dapat merancang skenario secara mandiri. Simpulan yang dapat ditarik adalah bahwa kedua model kurikulum terpadu ini dapat dijadikan salah satu alternatif  model kurikulum terpadu khususnya dalam keterampilan menulis surat lamaran pekerjaan oleh guru-guru terkait di SMK. Job application letter  is one of   the  letters  that shall be mastered by vocational students  for  the preparation of  entering work. Currently, the skill to write a job application letter is taught in the subject of  KKPI (Computer and Information Processing Skill) relating to  the application of  data processing, meanwhile English and Indonesian are related  to  the content of  the letter. Two models of integrated curriculum are threaded and connected to encourage researcher to describe the implementation and examine the improvement of  student skill in writing the letter after using the model.The data were gathered using the techniques of  work, observation and interview. Meanwhile the data were processed by collecting, reducing, describing, analyzing and  summarizing  them. Basically  the  implementation  of   threaded  or  connected  cur-riculum has the similar aspects in terms of  the material which uses word processing application (Ms. Word) and English or Indonesian job application  letter. The dif ference between  the curricula  is  the threaded curriculum taught by a  team teaching of  KKPI, English and Indonesian teachers but the connected curriculum is only taught by one teacher, KKPI.Threaded or Connected curriculum triggers the improvement of  letter writing skill though there is only a slight dif ference. The advantage of  threaded curriculum is upon the team teaching consisted of  some teachers with some background and understanding that would benefit  the students. On the other hand, if   there is no coordination, the teacher will rely on each other so the basic competence would not be achieved due to lack of preparation to make a lesson plan. The advantage of  connected curriculum is the independency of  a teacher to make a lesson plan. In contract, it could be problematic if  KKPI teacher does not master the material of  writing an English and Indonesian job application letter so the lesson will only be dominated by KKPI subject.Regarding the advantages of  integrated curriculum in KKPI with basic competence of  operating data processing software with threaded as well as connected curriculum, vocational teacher shall implement both model especially in the competence of  writing a job application letter. Some concerns that shall be taken into consid-eration are: concept understanding, types of  model and steps of curriculum design by a need analysis.